Do místico ao político: uma leitura bakhtiniana do romance Quarup de Antonio Callado - Silva, André Plez (2015)
The present work had as objective analyzes the stylistic process of the romance Quarup (1967), of Antonio Callado, which interferes in the picture of the produced literature powder64, which explores and expresses the social way of your time, in other words, the disturbed period of the Military Dictatorship in Brazil. As general objective, we analyzed the architectural of the romance, where verified that the construction of the style is not treated of an individual and isolated choice, because it is linked to the sociological stylistic, being linked to the social life of the speech, tends in your form and content a determination with the concrete social context, tuning the social dialogue in the own speech and in all your elements, so much in formal level, as of content. Also as mark of the style, we tried to evidence the couple present refraction in the work, starting from the studies of Bakhtin on the phenomenon of the authorship, where the author-person's voice is refracted in the author-creator's voice, evidencing that Callado's romance is fruit of the journalistic and literary sphere. As specific objective was verified dialogically the course of the hero Nando, under the inclination of the dialogical relationships of Bakhtin, observing that the pilgrimage of the hero served as motto for the representation of the identity of the many brasis, that the author tried to recover starting from specific atmospheres and cut out historical, evidencing the Bakhtin‘s concept of cronotopo. Besides, the course of uneducated of Nando, that began as mystic, leaving heading for the politician, it shows the author's positioning in the attempt of forming an ideal hero, that would be a subject that if unhooks of the ideologies imposed by the colonialist culture of Brazil, arriving to the revolutionary that it struggles against the oppression of the totalitarian regimes, demonstrating the style, in other words, the authentic mark of the works enrolled in the years of lead. As theoretical validity, followed Bakhtin in your concepts of dialogism, otherness, style, cronotopo, exotopy, author-person and author-creator ([1926]; 1993; 2009; 2010; 2011; 2013), besides your commentators, such like Fiorin (2011), Brait (2012), Faraco (2013), Machado (1990), Marchezan (2015). The methodology of the research consisted of qualitative rising of bibliographical stamp of the russian philosopher's works, besides the inductive method, that consisted of the use and application of the methods of Bakhtin to arrive to the general. After the bakhtinian reading of Quarup, improved that the romantic gender is inserted in bedding it interns of the language, revealing the social diversity and the divergence of social voices that he contains, describing a reality plurilinguistic, pluridiscursive and plurivocal. The research proved that Quarup is a resistance romance during the dictatorship, because it shows a period of the culture and of the Brazilian history in a style that flows exactly of that historical moment, because they would not have the style didn't leave the moment, being the legitimate mark of the people's style, in other words, the cultural mark of Brazil.